Biaya Pasien Jaminan Kesehatan Nasional yang Menjalani Seksio Sesarea di RSUP Dr. Sardjito Yogyakarta - , ADI RAHMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Ease of access and timeliness in reaching emergency in obstetric care is necessary to save the mother and newborn. Delivery by caesarean section on emergency obstetric aims to save the mother and newborn. The amount of cost from the emergency obstetric care particularly caesarean section, was significantly higher compared to childbirth without complications. The implementation JKN (Jaminan Kesehatan Nasional) aims to overcome this programs. Government hospitals have a dilemma between the mission of serving the lower middle class society and the limited financial resources, as well as a variety of rules and bureaucracy. Casemix system on INA-CBGâs (Indonesian Case Base Groups) is grouping similar patient characteristics. Hospital will receive payments based on the average amount of cost by a group of diagnosis. Objective: Knowing the cost of the JKN patient who underwent cesarean section in Dr. Sardjito Hospital. Methods: The study design is a qualitative. Material and methods: JKN patients undergoing Caesarean section in January-July 2014 at the Hospital Dr. Sardjito included in the study. Patients were moved to the VIP treatment, VVIP, and suites in the exclusion. Patient cost data will be averaged and be detailed by characteristics. Results: A total of 136 patients undergoing caesarean section JKN during January-July 2014. Average cost of patients undergoing caesarean section was 10,337,411 rupiahs. The patient had severe preeclampsia ratas average cost 3,050,776 rupiahs higher than patients without severe preeclampsia. Patients with 4 disesases and complications had the difference in cost 16,995,952 rupiahs higher than patients without the disease. Patients with ICU care have an average higher cost than non-admission to the ICU in the amount of 3,340,288 rupiahs. Difference in average higher costs also occur on length of stay. Hospitalization class, duration stay in the delivery room, the induction or stimulation in the delivery room. and history of cesarean section is not leading to higher cost. Conclusion: The average cost of patients undergoing caesarean section was 10,337,411 rupiahs. complications of the disease and the patient's condition, severe preeclampsia, long hospitalization, ICU care, led to high costs in patients undergoing caesarean section. Keyword : cesarean section, cost, JKN, INA-CBGâs